The collection building and collection management practices of the University of the Philippines Film Center Archives a study - Ilogon, Faye V. (1997)
The undergraduate thesis, The Collection Building and Collection Management Practices of the University of the Philippines Film Center Archives: a Study, is a documentation of the current collection building and collection management policies and practices of the UPFC Archives. It was found that despite the existence of well-planned guidelines, the collection building and collection management operations are affected by factors like the budget, staffing, administrative processes, and the facilities which house the film collection.